Filtracja Cieczy w Złożu ze Szczeliną Poziomą - Salwa, K.; Walden, H. (Engineering Transactions, 1960)
The problem of symmetric filtration in a horizontal slot is considered. The computation of the rate of the outflow from the slot is reduced to the solution of LAPLACE'S equation with mixed boundary conditions. Using Hankel's integral transformation, solution is obtained in the form of a series in the roots of the BESSEL function. To verify experimentally the result, a number of measurements of pressure and flow rate have been performed on a filtration model. A confrontation of the theoretical and experimental results shows a discrepancy of 1,4 to 39% which is admissible for filtration problems.